Associations between negative life experiences and the mental health of trans and gender diverse young people in Australia: findings from Trans Pathways. Issue 5 (8th April 2020) - Strauss, Penelope; Cook, Angus; Winter, Sam; Watson, Vanessa; Wright Toussaint, Dani; Lin, Ashleigh
Abstract: Background: Trans and gender diverse (TGD) young people worldwide experience high rates of poor mental health; however, these rates were unknown in Australia. In addition, how negative life events affect the mental health of TGD young people has been largely unexplored. Methods: This paper reports on novel mental health findings of Trans Pathways, the largest study ever conducted in Australia with trans (transgender) and gender diverse young people ( N = 859; aged 14–25 years). The study was an anonymous online cross-sectional survey undertaken in 2016. Logistic and linear regression models were used to test associations between mental health outcomes and negative life experiences. Results: TGD young people in Australia experience high levels of mental distress, including self-harming (79.7%), suicidal thoughts (82.4%), and attempting suicide (48.1%). Three in four participants had been diagnosed with depression and/or anxiety (74.6% and 72.2%, respectively). Many TGD young people had been exposed to negative experiences such as peer rejection (89.0%), precarious accommodation (22.0%), bullying (74.0%), and discrimination (68.9%). Most poor mental health outcomes were associated with negative experiences. The strongest associations were found for precarious accommodation and issues within educational settings. For example, participants with a prior suicide attempt were almost six times more likely to have experienced issues with accommodation, including homelessness. Conclusions: The current results highlight the urgent need for better mental health care and provide insight into areas for targeted mental health interventions. These findings are pertinent for clinicians working with trans young people and wider society.